2021
DOI: 10.3390/catal11030365
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Catalytic Hydrogenation of Bromate in Water Phase

Abstract: The presence of bromate in water sources generates environmental concern due to its toxicity for humans. Diverse technologies, like membranes, ion exchange, chemical reduction, etc., can be employed to treat bromate-polluted water but they produce waste that must be treated. An alternative to these technologies can be the catalytic reduction of bromate to bromide using hydrogen as a reducing agent. In this review, we analyze the research published about this catalytic technology. Specifically, we summarize and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…In addition, increasing the concentration of the coexisting anions leads to enhanced inhibition effects [50,51]. It was also reported that the catalyst deactivation appears more significant when harder waters are treated (high content of Ca 2+ and Mg 2+ ), resulting in an obstruction of the catalyst by the deposition of calcium salts, making it more difficult to access the catalytic active centers [10]. Regardless, the ball-milled sample clearly demonstrated complete bromate reduction during the whole treatment time from both the water well sample and the WTP sample, although it contained various competing ions.…”
Section: Application To Real Drinking Watermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, increasing the concentration of the coexisting anions leads to enhanced inhibition effects [50,51]. It was also reported that the catalyst deactivation appears more significant when harder waters are treated (high content of Ca 2+ and Mg 2+ ), resulting in an obstruction of the catalyst by the deposition of calcium salts, making it more difficult to access the catalytic active centers [10]. Regardless, the ball-milled sample clearly demonstrated complete bromate reduction during the whole treatment time from both the water well sample and the WTP sample, although it contained various competing ions.…”
Section: Application To Real Drinking Watermentioning
confidence: 99%
“…The support of the metal phase can influence the density, size, and morphology of the active centres of the metal and, as a result, the activity of the catalyst. Different supports such as AC, multi-walled carbon nanotubes (MWCNT), and titanium dioxide (TiO 2 ) were reported [8][9][10] as supports for the metal phase, having shown that the interaction of the support with the metallic phase is responsible for substantial differences in activity. In general, distinct catalytic performances were reported when using catalysts with similar metallic loadings but supported on different materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that catalyst deactivation is more significant when the treated water is harder; that is, it contains higher levels of Ca 2+ and Mg 2+ . This leads to clogging of the catalyst due to salt deposition, making access to the catalyst difficult [51].…”
Section: Before Reactionmentioning
confidence: 99%
“…Catalytic BrO 3 − reduction technology has a series of distinct advantages. Due to its fast reaction kinetics towards contaminants, high efficiency, and extended durability, bromate reduction by nanoscale heterogeneous catalysts could be potentially applied to current groundwater and surface water treatment systems [ 6 ]. Based on the evaluation of significant environmental factors, these technologies exhibited reliable stability and cost-effectiveness [ 7 ].…”
Section: Introductionmentioning
confidence: 99%